«
  
»
MOSTRAR DESENVOLVIMENTO
1. Simplificando a expressão a³. (a² + a³) : a^5 encontramos:
a) a³
b) 1+a
c) 1-a
d) a + a²
2. a expressão:
6x³-9x / 3x²
é igua a:
3. Simplificando a expressão x²y-y³/x-y obtemos:
a) x - y²
b) x² - y²
c) xy-y²
d) xy² + y


RESOLVENDO

1. Simplificando a expressão a³. (a² + a³) : a^5 encontramos:
a³. (a² + a³) = a³. a²(1 + a) = a^5(1+a)==> 1 + a
a^5 a^5 a^5
letra B
a) a³
b) 1+a
c) 1-a
d) a + a²
2. a expressão:
6x³-9x = 3x²( 2x - 3 ) ==> 2x - 3
3x² 3x²
3. Simplificando a expressão x²y-y³/x-y obtemos:
x²y-y³ = y(x²-y²) ==> y(x+y)(x-y) ==> y(x+y) ==> xy + y²
x-y (x-y) (x-y)
sem resposta
a) x - y²
b) x² - y²
c) xy-y²
d) xy² + y



TAREFAS SIMILARES: